Delivering on the promise of competency based medical education – an institutional approach - Dagnone, Damon; Stockley, Denise; Flynn, Leslie; Egan, Rylan; van Wylick, Richard; McEwen, Laura; Walker, Ross; Reznick, Richard (Canadian Medical Education Journal, 2019)
The Royal College of Physicians and Surgeons of Canada (RCPSC) adopted a plan to transform, over a seven-year horizon (2014-2021), residency education across all specialties to competency-based medical education (CBME) curriculum models. The RCPSC plan recommended implementing a more responsive and accountable training model with four discrete stages of training, explicit, specialty specific entrustable professional activities, with associated milestones, and a programmatic approach to assessment across residency education. Embracing this vision, the leadership at Queen’s University (in Kingston, Ontario, Canada) applied for and was granted special permission by the RCPSC to embark on an accelerated institutional path. Over a three-year period, Queen’s took CBME from concept to reality through the development and implementation of acomprehensive strategic plan. This perspective paper describes Queen’s University’s approach of creating a shared institutional vision, outlines the process of developing a centralized CBME executive team and twenty-nine CBME program teams, and summarizes proactive measures to ensure program readiness for launch. In so doing, Queen’s created a community of support and CBME expertise that reinforces shared values including fostering co-production, cultivating responsive leadership, emphasizing diffusion of innovation, and adopting a systems-based approach to transformative change.